Unveiling the nutritional and antioxidant properties of brown algae resources (Dictyota J.V. Lamouroux) from the Bay of Bengal and Arabian Sea, Indian coast - P. Chellamanimegalai; Geetanjali Deshmukhe; Amjad K. Balange; P. Layana (Heliyon)
Brown algae are increasingly recognized as a promising alternative food source due to their nutritious and bioactive properties. This study investigates the biochemical constituents and antioxidant properties of eight Dictyota species collected from the East and West coast of India, providing insights into their nutritional status for fulfilling dietary requirements. The analysis revealed significant levels of protein (6.67–19.27 %), ash (16.48–52.55 %), lipids (1.37–4.55 %), carbohydrates (25.98–57.07 %), and digestible energy (186.43–311.88 Kcal/100 g), indicating their potential as functional foods. Dictyota species were enriched in mineral contents, including Na (113–1973 mg/100 g), K (71–1487 mg/100 g), Ca (1773–11,108 mg/100 g), Mg (515–1138 mg/100 g), Fe (248–887 mg/100 g), Zn (1.2–3.6 mg/100 g), Cu (0.89–7 mg/100 g), and Mn (1–38 mg/100 g). Among these, Ca, Fe, Mg, and Mn obtained from 5.2 g of Dictyota contributed significantly (>15 %) to the Recommended Dietary Allowance for Indians, highlighting their potential to address dietary mineral gaps. Similarly, chlorophyll a (1.351–3.478 mg g−1), chlorophyll C1+C2 (0.664–1.720 mg g−1), total carotenoids (0.427–1.763 mg g−1), and fucoxanthin (0.058–1.741 mg g−1) contents were notably high. Antioxidant properties were evaluated through total phenols and in-vitro antioxidant activities using different solvents, showing species-specific and solvent-specific variations (p < 0.05). These antioxidants can help reduce the risk of chronic diseases, improve immune function, and promote overall well-being. The findings of this study provide comprehensive insights into the nutritional and antioxidant potentials of Dictyota, facilitating future applications in nutrition and health promotion.